The Internal Organization of Speleothems - Self, Charles A. (Acta Carsologica, 2016)
Siga se izloča kot sekudarni jamski mineral, njeno notranjo zgradbo lahko preučujemo z mineraloškimi metodami. Ontogenija mineralov je metoda, razvita v Rusiji, pri kateri so posamezni kristali in njihovi agregati preučevani kot fi zična telesa in ne kot mineralna vrsta. Članek podaja kratek vodnik po terminologiji ontogenije s poudarkom na jamskih mineralih. Speleothems are secondary cave mineral deposits whose internal organization can be studied by mineralogical techniques. The ontogeny of minerals is a technique developed in Russia whereby individual crystals and their aggregates are studied as physical bodies rather than as mineral species. This paper gives a concise guide to the terminology of ontogeny, as applied to cave mineral deposits.